Identity-Based Blind Signature Scheme with Message Recovery - Salome James; T. Gowri; G.V. Ramesh Babu; P. Vasudeva Reddy (Institute of Advanced Engineering and Science, 2017)
Blind signature allows a user to obtain a signature on a message without revealing anything about the message to the signer. Blind signatures play an important role in many real world applications such as e-voting, e-cash system where anonymity is of great concern. Due to the rapid growth in popularity of both wireless communications and mobile devices, the design of secure schemes with low-bandwidth capability is an important research issue. In this paper, we present a new blind signature scheme with message recovery in the ID-based setting using bilinear pairings over elliptic curves. The proposed scheme is unforgeable with the assumption that the Computational Diffie-Hellman problem is hard. We compare our scheme with the related schemes in terms of computational and communicational point of view.